Application of intermittent ball milling to enzymatic hydrolysis for efficient conversion of lignocellulosic biomass into glucose. (February 2021) - Wu, Yingji; Ge, Shengbo; Xia, Changlei; Mei, Changtong; Kim, Ki-Hyun; Cai, Liping; Smith, Lee M.; Lee, Jechan; Shi, Sheldon Q.
Abstract: Hydrolysis of lignocellulosic biomass is important for isolation of glucose in a biorefinery. In this research, intermittent ball milling was applied to facilitate and enhance enzymatic hydrolysis of dilute acid-pretreated lignocellulosic biomass, with the highest glucose yield of 66.5% at a low enzyme dose (10 FPU g −1 glucan) over 24h. In comparison, the yield for the typical liquid-state enzymatic hydrolysis was only 38.7% for 24h, although it reached 69.0% after 72h. Glucose yield increased further to 84.7% using the delignified lignocellulosic biomass after a 24 h intermittent ball milling process. The observed glucose yield (24h) is comparable to the desired 80% (72h) milestone yield set by the US DOE but only with a three times shorter processing time despite the differences in experimental conditions. Further, the amount of solvent needed for the intermittent ball milling process was 25-folds reduced, compared with typical hydrolysis. Intermittent ball milling was useful for enhancing the performance of enzymatic hydrolysis with favorable adsorption of enzymes into cellulose. It also exhibited high efficiency in enzymatic hydrolysis of lignocellulosic biomass relative to continuous ball milling. It was suggested that ball milling could help distribute enzymes into cellulose, however, continuous ball milling would simultaneously separate enzymes from cellulose before the completion of hydrolysis. Therefore, intermittent ball milling could facilitate enzymes distribution and leave enough time for them to consume the boned cellulose chains. This technology should be beneficial for development of more effective and environmentally benign approaches to enzymatic hydrolysis to effectively isolate glucose from lignocellulosic biomass. Graphical abstract: Image 1 Highlights: In-situ intermittent ball milling was introduced to promote enzymatic hydrolysis. Processing time of new technology was 1/3 of the conventional enzymatic hydrolysis. Use of solvent was only 1/25 of the liquid-state enzymatic hydrolysis. Mechanism of intermittent ball milling enzymatic hydrolysis was illustrated.